Power and Uncertainty: An Analysis of the Structure of an Emergency Ward in a General Hospital - Williams, Peter (My University, 1965)
This study is concerned with analyzing the ways in which the members of an organization faced with problems of unpredictability and uncertainty, adapt to the situation and achieve some degree of control over it. Chapter 1 describes the organization within which the study was conducted, and also discusses the methodology employed. Chapter 2 reviews the literature pertinent to the problem, both on the spheres of organization theory and medical sociology. Chapter 3 describes the role and mode of adaptation of the physician to the situation. Chapter 4 examines the role of the head nurse and her relations with other ward members. Chapter 4 examines the role of the head nurse and her relations with other ward members. Chapter 5 provides an analysis of the sources of tension and conflict in the ward and the final chapter contains a summery of the previous arguments and a discussion of their pertinence to sociological theory.
Keywords: power and uncertainity; emergency ward; general hospital